Genetic Diversity of Plant Growth Promoting Rhizobacteria of Bacillus sp. Based on 16S rRNA Sequence and Amplified rDNA Restriction Analysis - SYAMSUL BAHRI SYAMSUL BAHRI; ARIS TRI WAHYUDI; NISA RACHMANIA MUBARIK (Indonesian Society for microbiology, 2009)
Plant-growth promoting rhizobacteria (PGPR) are rhizosphere associated soil-borne bacteria that can enhance plant growth and inhibit the development of root pathogens. Many soil bacteria have been used as PGPR, and one of them is Bacillus sp. The implementation of PGPR is constrained by genotype fluctuation that makes it inactive on the rhizosphere. Our previous study had characterized and revealed that 11 Bacillus sp. isolated from the soybean plant rhizosphere were PGPR. To asses and compare the genetic diversity of these isolates, Amplified Ribosomal DNA Restriction Analysis (ARDRA) and DNA sequence analysis of 16S rRNA were conducted. The construction of Neighbor-joining trees and bootstrap analysis of 100 resamples of ARDRA and 16S rRNA gene sequences were performed using Treecon software for windows ver. 1.3b. ARDRA analysis was done by using four restriction enzymes (RsaI, HaeIII, CfrI and HinfI), resulting in four phylotypes, respectively phylotype I (Bacillus sp. Cr24, Cr33, Cr64 and Cr68), phylotype II (Bacillus sp. Cr 31 and Cr66), phylotype III (Bacillus sp. Cr44 and Cr71) and phylotype IV (Bacillus sp. Cr67, Cr28 and Cr69). Results of BLASTN from 16S rRNA gene sequences showed that these isolates are genetically diversed. The evolution relationship of Bacillus sp. could be shown by the 16S rRNA gene sequences analysis, while ARDRA based on the digestion sites showed their variability.